2018
DOI: 10.1002/anie.201808560
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Amide Bond Formation from Methyl Esters

Abstract: Despite being one of the most important and frequently run chemical reactions, the synthesis of amide bonds is accomplished primarily by wasteful methods that proceed by stoichiometric activation of one of the starting materials. We report a nickel-catalyzed procedure that can enable diverse amides to be synthesized from abundant methyl ester starting materials, producing only volatile alcohol as a stoichiometric waste product. In contrast to acid- and base-mediated amidations, the reaction is proposed to proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…Similar reductive coupling reactions using chromium catalysts have also been recently reported by Zeng and co-workers [23]. Nickel has also been employed by Newman and co-workers for direct amidation of methyl esters at high reaction temperatures [24]. Therefore, there is a growing interest in the use of esters as substrates for direct amidation reactions.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar reductive coupling reactions using chromium catalysts have also been recently reported by Zeng and co-workers [23]. Nickel has also been employed by Newman and co-workers for direct amidation of methyl esters at high reaction temperatures [24]. Therefore, there is a growing interest in the use of esters as substrates for direct amidation reactions.…”
Section: Introductionsupporting
confidence: 62%
“…Molecules 2020, 25, 1040 2 of 9 methyl esters at high reaction temperatures [24]. Therefore, there is a growing interest in the use of esters as substrates for direct amidation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of Ni(CO) 4 complexes by Mond in 1888 [1], organo-nickel chemistry saw comprehensive developments. Nickel-based catalysts proved their effectiveness in several types of reactions, including cross-couplings [2], methanations [3,4], nucleophilic allylations [5,6], oligomerizations [7], hydrodeoxygenations [8], and hydrogenations [9]. This last reaction can make use of Raney ® -nickel, which is the most popular catalyst in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Theu se of abundant methyl esters is ap articularly appealing alternative to more activated surrogates.However, the absence of coordinating and/or electron-withdrawing functionality renders oxidative addition into the strong C(acyl)ÀOb ond as ignificant challenge.G arg,H ouk, and co-workers first demonstrated that methyl esters could be activated for cross-coupling reactivity [7] with the use of aN i catalyst. [8] While this transformation was limited to methyl naphthoate derivatives activated by stoichiometric Al-(OtBu) 3 ,l ater reports by the groups of Rueping, [9] Yamagu-chi, [10] and ourselves [11] demonstrated that these limitations could be overcome,albeit at temperatures from 140 to 170 8 8C (Scheme 1B). DFT studies support the hypothesis that aN i 0 catalysts is capable of oxidatively adding to the strong C(acyl) À Obond of amethyl ester with reasonable activation energies, [8,12] though formation of the corresponding acyl-Ni complex is thermodynamically uphill and likely reversible.…”
mentioning
confidence: 99%
“…We began our investigation with the activation of methyl ortho-allylbenzoate (1a)w ith catalytic Ni(cod) 2 .O ur related amidation reaction with IPr (bis(2,6-diisopropylphenyl)imidaze-2-ylidene) as ligand required 140 8 8Ctoachieve appreciable conversion. [11] With 4-methoxybenzeneboronic acid (2a) as an ucleophile,a n1 8% yield of the indanone product 3a was observed at 90 8 8Cw ith K 3 PO 4 as the base in toluene (Table 1, entry 1). Thec hoice of ligand was highly important (entries 2-6), with the saturated NHC ligand SIPr being best (entry 7), giving 41 %y ield with the remainder of the mass balance being isomerized 1a.…”
mentioning
confidence: 99%